INDEPENDENT WORK ON A FOREIGN LANGUAGE PROFESSIONAL ORIENTATION IN THE SYSTEM PROFESSIONAL TRAINING OF THE FUTURE TEACHER - Skrylnyk, N.O. (Pedagogy of Higher and Secondary Education, 2006)
The article is dedicated to the capabilities of a foreign language during modern teacher’s personality formation; dynamics of the English language analysis in a system of vocational training for future teacher is traced.